2018
DOI: 10.3390/rs10111751
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Crop Identification from Multi-Temporal Multi-Sensor Satellite Imagery Using Object-Based Approach: A Case Study from Almería (Spain)

Abstract: M.A.A.); faguilar@ual.es (F.J.A.)Abstract: A workflow headed up to identify crops growing under plastic-covered greenhouses (PCG) and based on multi-temporal and multi-sensor satellite data is developed in this article. This workflow is made up of four steps: (i) data pre-processing, (ii) PCG segmentation, (iii) binary pre-classification between greenhouses and non-greenhouses, and (iv) classification of horticultural crops under greenhouses regarding two agronomic seasons (autumn and spring). The segmentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 57 publications
(106 reference statements)
0
20
0
Order By: Relevance
“…Our CDT serves as an exploratory tool for data-driven discovery and prediction to gain new insights on LULC in central EPEs. Although other classifiers could achieve better classification results, CDT provides clear decision rules with fixed threshold values that can be used in future research without any training phase [44]. It has been shown that the CART algorithm can provide stable performance and reliable results in machine learning and data mining research [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our CDT serves as an exploratory tool for data-driven discovery and prediction to gain new insights on LULC in central EPEs. Although other classifiers could achieve better classification results, CDT provides clear decision rules with fixed threshold values that can be used in future research without any training phase [44]. It has been shown that the CART algorithm can provide stable performance and reliable results in machine learning and data mining research [45].…”
Section: Discussionmentioning
confidence: 99%
“…It has been used to identify spectral bands with the highest discriminative capabilities between classes and low misclassification rates [45]. Classification utilizing the DT algorithm has already been applied in identifying both field-grown and greenhouse crops from remote sensing data with excellent and robust results [44]. However, the CDT found in this study can become unstable, as a change in one node affects all of the nodes that are connected below.…”
Section: Discussionmentioning
confidence: 99%
“…The exhibited plastic greenhouses belong to both arch and single plastic greenhouses, which are the main types in China for planting various vegetables and typically feature a size of 400-1200 m² [40]. In other areas, such as in Spain even larger cover areas are characteristic (around 10 000 m 2 ) [37]. Tomato, pimento, tabasco, cucumber, muskmelon, and watermelon are the most representative crops under the plastic greenhouses in this area.…”
Section: A Study Areamentioning
confidence: 99%
“…Methods of spectral unmixing in combination with textural features are shown to be a prerequisite for high mapping accuracies of plastic greenhouses on medium resolution images of 91.2% [21]. However, for assessing the performances of different classification products based on medium resolution images [37], VHR images are always needed to verify and correct the mapping accuracies [38], [39]. Although medium resolution images seem more economical, reported accuracies are significantly lower.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, Geographic Object-Based Image Analysis can be used to delineate spatial regions by grouping adjacent pixels into homogeneous areas according to the objectives of the study [23,24]. For biodiversity research, image segmentation has been used to automatically derive homogeneous vegetation units based on spectral [25] or a combination of spectral and structural (height) information [16,26].…”
Section: Remote Sensing For Ecotope Mappingmentioning
confidence: 99%